ApoE4 - the most prevalent genetic risk factor for Alzheimer's disease - Michaelson, Daniel (Henry Stewart Talks, 2012)
ApoE4 the most prevalent genetic risk factor of Alzheimer's disease, The apoE4 molecule, The associated brain pathology in man, The mechanisms underlying the pathological effects of apoE4, The role of lipids in mediating the effects of apoE4, The role of Amyloid-beta in mediating the effects of apoE4, ApoE4 receptors, ApoE4 catabolism, ApoE4 targeted therapeutic approaches, Therapeutic approaches based on the apoE4 molecule, Therapeutic approaches based on preventing pathologic interactions with other systems